Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.6007/ijarbss/v11-i9/10754
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perceptions on the University Social Responsibilities of a Malaysian Private University: Does Gender Matter?

Abstract: University social responsibility (USR) has emerged tremendously as an important area supporting the Sustainable Development Goals (SDGs). Today, universities have realized the significance of being ethical in their operations to attract various stakeholders, especially the students (customers). However, the influence of social responsibility practices in university settings remains understudied as USR is a newly emerging concept. The purpose of this study was to examine the students' perception of USR and test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
(45 reference statements)
1
4
0
Order By: Relevance
“…With regard to the study's secondary goal, which is to determine how students' demographic information affects their views on CSR, differentiation based on age, level of education, and professional experience was supported by the data in this study, which strongly indicates that students' CSR perceptions is influenced by the sociodemographic variables which is in line with the findings of (Almutawa and Hewaidy, 2020) and is in contradiction to the findings of (Anand and Singh, 2021;Burcea and Marinescu, 2011;Pätäri et al, 2017;Teixeira et al, 2018;Ugwuozor, 2020). Whereas the t-tests on gender and civil status depicted that there is no statistical relationship between these two variables and the reduced dimensions of students' impression of CSR which is in line with finding of (Almutawa and Hewaidy, 2020; Chan et al, 2021).…”
Section: Discussionsupporting
confidence: 82%
“…With regard to the study's secondary goal, which is to determine how students' demographic information affects their views on CSR, differentiation based on age, level of education, and professional experience was supported by the data in this study, which strongly indicates that students' CSR perceptions is influenced by the sociodemographic variables which is in line with the findings of (Almutawa and Hewaidy, 2020) and is in contradiction to the findings of (Anand and Singh, 2021;Burcea and Marinescu, 2011;Pätäri et al, 2017;Teixeira et al, 2018;Ugwuozor, 2020). Whereas the t-tests on gender and civil status depicted that there is no statistical relationship between these two variables and the reduced dimensions of students' impression of CSR which is in line with finding of (Almutawa and Hewaidy, 2020; Chan et al, 2021).…”
Section: Discussionsupporting
confidence: 82%
“…After running the F-test in G*Power 3.1.9.2 software, a sample size of 92 was calculated for this research study with an effect size of 0.15, a power of 80, and 5 predictors. Thus, the sample utilized in the statistical analysis was deemed suitable, as per (Chan, et al, 2021), which included 200 valid responses. (Sekaran, 2006) suggested that a sample size ranging from 30 to 500 is deemed suitable for research in the field of social science.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, private HE institutions in Malaysia have transformed (Jayabalan et al, 2021). Therefore, there is a concern that Private Higher Education Institutions in Malaysia may not meet needs of the students as well as the industry (Anis et al, 2018;Chan et al, 2021). Ali et al (2016) and Khalifa et al (2021) found that HE service quality, administrative quality, core educational quality, support facilities quality, reputation and program issues ensure student satisfaction.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…In recent years, private HE institutions in Malaysia have transformed (Jayabalan et al ., 2021). Therefore, there is a concern that Private Higher Education Institutions in Malaysia may not meet needs of the students as well as the industry (Anis et al ., 2018; Chan et al ., 2021). Ali et al.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation